Conclusiones sobre la adopción de normas internacionales de auditoría (nia) en américa - Español, Guillermo Gabriel (2014)
This work allowed to make a synthetic presentation of the status of adoption of International Standards on Auditing (ISA) of IFAC in the different countries of America. Each country began making processes of adoption and harmonization of local auditing standards to align with international standards. These processes have been developed in different ways ranging from the readjustment of local regulations to the literal adoption of ISAs. These processes did not occur simultaneously. Homogenization of standards in an internationally level involves a challenge to the accounting profession. The convergence to uniform audit standards in the world is a priority because it promises an improvement in the quality of professional services, which will result in increased value to users of audited information. ISAs of IFAC provides an acceptable uniform universal standard for this purpose.